MANAJEMEN PEMBELAJARAN TEACHING FACTORY DALAM MENUMBUHKAN JIWA KEWIRAUSAHAAN PESERTA DIDIK - Yunus, Muhammad Yunus Rangkuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by concerns in preparing competent workers according to the expectations of the business and industrial world (DUDI), SMK needs to make new breakthroughs, one of which is with the Teaching Factory learning program so that students are more skilled, independent, competitive and entrepreneurial. The purpose of this study is to determine and analyze the Teaching Factory Learning Management in Cultivating Students' Entrepreneurial Spirit. The Grand Theory used is the POAC management function, namely Planning, Organizing, Actuating, Controlling (G.R Terry). The research method used is a case study through a qualitative approach. Data collection techniques include in-depth interviews, observations, and documentation studies. The results of this study reveal that: This study shows that the Teaching Factory (TEFA) program in SMK is effective in fostering students' entrepreneurial spirit through the application of the POAC management function. Industry-based curriculum planning, organizing tasks between schools and industrial partners, implementing real production by students, and periodic evaluations have been carried out well. Although there are obstacles such as limited facilities and budget, solutions such as increasing cooperation with industry and adjusting the curriculum have been identified. Principal leadership that supports innovation and collaboration plays an important role in the successful implementation of TEFA, reflecting the entrepreneurial attitude of students who dare to take risks, are creative, and competitive. Keywords: Teaching Factory Learning Management, Cultivating, Entrepreneurial Spirit